B-site mixed cationic tetrahedral layer confined the concentration and mobility of interstitial oxygen in mellite family. Issue 11 (28th February 2023) - Li, Xiaohui; Wei, Xianyi; Wang, Xiaoge; Lou, Chenjie; Zhang, Wenda; Xu, Jungu; Luo, Zhaoji; Tang, Mingxue; Deng, Sihao; He, Lunhua; Xing, Xianran; Sun, Junliang; et al.
Abstract : The subtle difference in the cationic size and covalent bonding between Ga and Ge enables B-site mixed Ga/Ge tetrahedral centers to confine the concentration and mobility of interstitial oxygen in mellite family. Abstract : Melilite-type oxide ion conductors usually were observed in pure gallate compounds. Here a new mellite interstitial oxide ion conductor Ca2− x La x Ga2 GeO7+ x /2 (0 ≤ x ≤ 0.15) was developed by the substitution of La 3+ for Ca 2+ in Ca2 Ga2 GeO7 containing mixed GaO4 /GeO4 tetrahedral layers. Neutron powder diffraction data indicated that the introduced interstitial oxide ions were accommodated in the distorted pentagonal rings, close to the coordination environment of (Ga2/Ge)O4 containing terminal oxygen. Defect formation energy calculations further reveal that the interstitial oxygen not only favors to approach the GaO4 tetrahedra, in agreement with studies of other pure gallate systems, but also is confined to the GeO4 tetrahedra. Bond-valence-energy landscape calculations and molecular dynamics simulations revealed that the interstitial oxide ions were transported among the pentagonal rings within the tetrahedral layers through a cooperative mechanism involving the synergistic knock-on motion between interstitial and framework oxygens. In Ca2 Ga2 GeO7, the La 3+ substitution for Ca 2+ only extended up to x = 0.15, which is much lower than those in the La–(Ca/Sr/Ba) based gallate mellites. The x = 0.15 composition resulted in oxide ion conductivities ∼2.79 × 10 −5 S cm −1 to 1.68 × 10 −3 S cm −1, with oxygen transport numbers of ∼92.65%, two orders of magnitude higher than that of the parent material. However, compared with pure gallate melilite interstitial oxide ion conductors with the same interstitial oxide ion concentrations, Ca1.85 La0.15 Ga2 GeO7.075 has about one order of magnitude lower conductivity. The lower interstitial oxide ion concentration and conductivity in Ca2− x La x Ga2 GeO7+ x /2 reveal that although Ge 4+ has similar chemical properties to the adjacent Ga 3+, the subtle differences in size and the resultant covalent bonding ability make the mixed GaO4 and GeO4 tetrahedral layers in mellite unfavorable for accommodation and transportation of interstitial oxygens.